SEBUAH STUDI TERHADAP KEMAMPUAN SISWA SEMESTER EMPAT PROGRAM STUDY BAHASA INGGRIS UNIVERSITAS RIAU DALAM MEMILIH KATA PENGHUBUNG - Elmi Rahma; Fakhri Ras; H.M. Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this descriptive research was to describe the students’ ability in choosing conjunctions. The sample of this research was the fourth semester students of English Study Program of Universitas Riau. There were 29 students participating as the sample of this research. The data were quantitative and the instrument of the research was a set of multiple choice structure test which consists of 40 questions about choosing the correct conjunctions to complete English sentences. The collected data were analyzed by calculating the scores of the students in answering the test and classified them to a certain level of ability in choosing conjunctions. The result showed that 3 out of 29 students (10.34%) were in the excellent level of ability, 6 students (20.69%) were in the good level of ability, 8 students (27.59%) were in the average level and 12 students (41.38%) were in the poor level. The students’average score was 52.67. This meant that the students’ ability in choosing conjunctions was in average level of ability. The most difficult type of conjunction for the students is subordinating conjunctions with the mean score 49.48 whereas the easiest one is coordinating conjunctions with the mean score 56.90. This research recommended the students to study more about subordinating conjunctions by practicing to answer questions to make them more familiar with subordinating conjunctions. Future studies should focus on how to improve the student’s ability in choosing conjunctions.